Community engagement for disaster preparedness: A systematic literature review. (October 2020) - Ryan, Barbara; Johnston, Kim A.; Taylor, Maureen; McAndrew, Ryan
Abstract: Disaster management agencies invest differing levels of resources into guiding communities to get ready for a range of hazards, and are increasingly turning to community engagement as a way of increasing preparedness. This paper presents a systematic literature review that reports on the effect of community communication and engagement techniques that have been used in a hazard preparedness context. The review findings suggest that most community engagement techniques are effective in generating some level of increased preparedness. For techniques that were found not to work, lack of benchmarking research, context and skill levels of those implementing the engagement were thought to be at fault rather than structural or conceptual problems with the technique itself. Face to face techniques were more consistently successful than mass media campaigns. However, all of the intervention types reported had some measure of success, even though there were individual failures. The 41 studies included used a wide variety of research methods that also varied greatly in rigor and replicability. Agency efforts to engage communities in preparedness should include a wide range of techniques that work together to change behaviour, including face-to-face community engagement that triggers and supports community-led preparedness activity. Highlights: This paper presents a systematic literature review of the effectiveness of community engagement techniques for preparedness. Most CE techniques have some effect on increased preparation activity. Measurement and evaluation of community engagement were inconsistent. Aims/objectives focus on 'getting ready' rather than saving lives and reducing losses. Many sample studies were low quality, reflecting need for rigor in design and reporting.